Redetection of Cervical Human Papillomavirus Type 16 (HPV16) in Women With a History of HPV16 - Moscicki, Anna-Barbara (Oxford University Press, 2013)
Background. The purpose of this study was to examine the rate of and risks for cervical human papillomavirus type 16 (HPV16) redetection in women with documented or suspected HPV16 infection. Methods. A convenience sample of women aged 13–21 years were seen at 4-month intervals for HPV DNA testing and cytology. Serum samples were obtained at baseline and annually. Results. A total of 1543 women entered the study. Of the 295 women with detection of HPV16 DNA and subsequent clearance, 18.1% had HPV16 redetected by 8.5 years (88% cleared this second detection by 3 years). Of the 247 women who had antibodies to HPV16 and were HPV16 DNA negative at baseline, 15.3% had HPV16 redetected by year 5. Risks for redetection included douching, current use of medroxyprogesterone, reporting >1 sex partner or having a new sex partner, and having a sexually transmitted infection. Development of cervical intraepithelial neoplasia 2/3 was rare in women with redetection, except for those with prevalent HPV16 infection. Conclusions. Reappearance of HPV16 DNA was observed in 18% of women. Most are associated with sexual exposure and appear benign. Interpretation of the studies is more complex in women with prevalent infections as it appears that this small subset reflects women with persistence already present at entry.